Education Of Moral Principles in Future Construction Players - Fadzida, Ismail; Noor Azlinna, Azizan; Nurhaizan, Mohd Zainudin; Suziyana, Mat Dahan; Lee, Chia Kuang (Publisher Universiti Malaysia Pahang, 2012)
In Malaysia, the Code of Ethics for Contractors (CIDB, 2010) is used as a guide for contractors in carrying out the construction works. The degree of moral behaviour in the building and construction industry has often been a concern and as a beginning, this article will look into the attitude and stance of Quantity Surveying students, for the reason that the program will produce significant construction players in the near future. A survey was conducted to the students prior to lectures to examine the students’ attitudes to various moral-related scenarios. This article presents the results which show that there is still room for improvement in the aspect of moral behavior in construction industry.